2020
DOI: 10.1007/s00038-020-01518-9
|View full text |Cite
|
Sign up to set email alerts
|

Engaging traditional barbers to identify and refer newborns for routine immunization services in Sokoto, Nigeria: a mixed methods evaluation

Abstract: Objectives This study evaluates the effectiveness of an intervention that engaged traditional barbers to inform parents about the importance of vaccination and then refer newborns for vaccination services. Methods We conducted a pre-post quasi-experimental study (n = 2639) to evaluate changes in the coverage of three birth antigens among children aged 0–5 months in response to the intervention. We also conducted in-depth interviews and focus group discussions to assess the enabling factors and challenges ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…A few were influenced by road shows followed by those who got influenced from seminars and lastly from phone call conversations with friends. This is in accord with the views of Ochonogor (2007) who observed that interpersonal communication is vital in nudging people to take decisions and accept innovations Also, the study by Dougherty et al (2020) agrees that Interpersonal communication has some advantages over other of communication forms, especially when the aim of the communicator is to achieve behavioural change.…”
Section: Discussion Of Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…A few were influenced by road shows followed by those who got influenced from seminars and lastly from phone call conversations with friends. This is in accord with the views of Ochonogor (2007) who observed that interpersonal communication is vital in nudging people to take decisions and accept innovations Also, the study by Dougherty et al (2020) agrees that Interpersonal communication has some advantages over other of communication forms, especially when the aim of the communicator is to achieve behavioural change.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…The study by Ozohu-Suleiman is related to the present one since they focused on interpersonal communication however, the points of divergence are that while his study dealt with polio in Kaduna State, the present one focused on sickle cell and rhesus factor in Bayelsa State. Dougherty et-al (2020) also carried out a study to evaluates the effectiveness of an intervention that engaged traditional barbers to inform parents about the importance of vaccination and then refer new-borns for vaccination services in Sokoto, Nigeria. Adopting a pre-post quasi-experimental to evaluate changes in the coverage of three birth antigens among children aged 0-5 months in response to the intervention, the results found that mothers who received a yellow referral card from a traditional barber were two to three times more likely to vaccinate their children with the three birth antigens.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…This included ‘baby tracking’ by volunteers to remind new mothers to vaccinate new-borns; and involving women and youth to help identify missed children [114] . [95] , [107] , [112] , [114] , [115] , [116] , [117] , [118] Engaging hard-to-reach communities 8 Engaging youth groups, leveraging existing structures, and using multi-pronged approaches to extend vaccination services, including screening tools for healthcare workers to identify vaccination needs and mobilising communities, increased coverage in hard-to-reach and security-challenged communities [90] , [92] , [95] , [113] , [119] , [120] , [121] , [122] Health education interventions for caregivers to increase vaccine awareness 4 Focused, short (5 min) health education sessions were more effective than longer (10–15 min), generic health promotion messages, and frequent vaccination messaging was preferred (i.e., not just during vaccination campaigns). Successful interventions included group health education for parents and pregnant women attending vaccination or antenatal clinics; and participatory learning on infant vaccination for older women.…”
Section: Resultsmentioning
confidence: 99%
“…In a highly patriarchal and conservative region where women’s mobility is often restricted, returning home without an immunized child gave husbands the impression that immunization was being exploited as an excuse to visit other places. This poses a challenge to spousal permission for future immunization of children and echoes other studies on the need to engage men through appropriate channels including traditional institutions (27).…”
Section: Discussionmentioning
confidence: 74%